Canine neutrophils cooperate with macrophages in the early stages of Leishmania infantum in vitro infection. (12th March 2019) - Pereira, Maria A.; Alexandre‐Pires, Graça; Câmara, Margarida; Santos, Marcos; Martins, Catarina; Rodrigues, Armanda; Adriana, Jéssica; Passero, Luiz Felipe D.; Pereira da Fonseca, Isabel; Santos‐Gomes, Gabriela
Summary: Leishmania infantum is the aetiological agent of human visceral leishmaniasis and canine leishmaniasis, both systemic and potentially fatal diseases. Polymorphonuclear neutrophils (PMN) are the first cells to phagocyte this parasite at the inoculation site, but macrophages (MØ) are the definitive host cells, ensuring parasite replication. The interaction between dog MØ, PMN and L infantum promastigotes was in vitro investigated. It was observed that promastigotes establish contact with blood monocyte‐derived MØ mainly by the tip of the flagellum. These cells, that efficiently bind and internalize parasites, underwent major morphological changes, produced nitric oxide (NO) and released histone H1 in order to inactivate the parasite. Transfer of intracellular parasites from PMN to MØ was confirmed by flow cytometry, using L infantum expressing a green fluorescent protein. The interaction of MØ with L infantum ‐infected PMN lead to NO production and release of extracellular traps, which may contribute to parasite containment and inactivation. This study highlights for the first time the diversity of cellular and molecular events triggered by the interaction between canine PMN and MØ, which can promote a reduction of parasite burden in the early phase of L infantum infection.